Faktor Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) - Simanjuntak, Vivin Aktika; Hasibuan, Rapotan (Jurnal Kebidanan Malakbi, 2024)
The escalating population of Indonesia is a pressing demographic challenge, contributing to a surge in the birth rate. Long-Term Contraceptive Methods (LTCM) offer a viable strategy for postponing and spacing pregnancies, thereby mitigating the adverse effects of population growth. However, LTCM utilization among women in the Glugur Health Center, Medan, remains notably low at 26.9%, indicating a significant gap in contraceptive access and adoption. To elucidate the factors influencing LTCM utilization, this study employed a cross-sectional research design. Data collection involved in-depth interviews with women residing within the Glugur Health Center's catchment area. The gathered data were subjected to rigorous analysis using univariate and bivariate statistical techniques. The findings revealed a strong correlation between Age (p=0,013; OR= 0,353), education (p=0.002; OR=3.594), the number of children (p=0.021; OR=2.545), knowledge (p=0.000; OR=4.278), attitudes (p=0.000; OR=10,818), source of information (p=0.017; OR=2,600), spouse's support (p=0.009; OR=3,135) and support of the health workers (p=0.028; OR=2.527) with LTCM utilization. The study's results underscore the critical role of comprehensive education and support in promoting LTCM adoption. Health officials and the Glugur Health Center should prioritize implementing targeted interventions to enhance women's knowledge and address any misconceptions regarding LTCM. Furthermore, fostering supportive environments, both within families and healthcare settings, is essential for encouraging consistent LTCM use. By addressing these key determinants, policymakers can significantly increase LTCM uptake and contribute to sustainable population growth in Indonesia.